Diphtheria Antibodies and T lymphocyte Counts in Patients Infected with HIV-1 - Speranza,Francisco A. B. (2012)
We assessed the IgG levels anti-diphtheria (D-Ab) and T cell counts (CD4+ and CD8+) in HIV-1 infected subjects undergoing or not highly active antiretroviral therapy (HAART). Approximately 70% of all HIV-1 patients were unprotected against diphtheria. There were no differences in D-Ab according to CD4 counts. Untreated patients had higher D-Ab (geometric mean of 0.62 IU/ml) than HAART-patients (geometric mean of 0.39 IU/ml). The data indicated the necessity of keeping all HIV-1 patients up-to-date with their vaccination.